Learner-centred corrective written feedback in primary EFL - Kuhar, Hana (ELOPE (Ljubljana), 2025)
Colour-coding and collaborative peer feedback are learner-centred techniques that support the development of writing skills in English as a foreign language (EFL), particularly in primary education. These techniques encourage creativity, foster collaboration, and increase learner engagement; however, their practical use among young learners remains underexplored. This article presents a systematic review of eight scholarly studies and theses published between 2010 and 2024, focusing on students aged 10 to 15, corresponding to the second and third cycles of the Slovenian primary school system. While the pedagogical value of these techniques is widely acknowledged, clear, age-appropriate guidelines for their classroom implementation are still lacking. To address this gap, the article synthesizes existing research and proposes a step-by-step instructional model adapted to EFL learners in this age group.
Keywords: angleščina kot tuji jezik; collaborative peer feedback; colour-coding feedback technique; corrective written feedback; English as a foreign language; pisna korektivna povratna informacija; second and third cycles of primary school; sodelovalna vrstniška povratna informacija; tehnika barvnega kodiranja; učenci drugega in tretjega vzgojno-izobraževalnega obdobja OŠ